Modelling the dynamic interactions between London's water and energy systems from an end-use perspective. (15th November 2018) - De Stercke, Simon; Mijic, Ana; Buytaert, Wouter; Chaturvedi, Vaibhav
Highlights: End-use interactions of the urban water-energy nexus help reduce future water demand. Interactions at the end use limit water system expansion requirements. Electricity must be decarbonised by order of magnitude for CO2 emissions targets. Abstract: Cities are concentrations of demand to water and energy systems that rely on resources under increasing pressure from scarcity and climate change mitigation targets. They are linked in many ways across their different components, the collection of which is termed a nexus. In industrialised countries, the residential end-use component of the urban water-energy nexus has been identified as significant. However, the effect of the end-use water and energy interdependence on urban dynamics had not been studied. In this work, a novel system dynamics model is developed with an explicit representation of the water-energy interactions at the residential end use and their influence on the demand for resources. The model includes an endogenous carbon tax based climate change mitigation policy which aims to meet carbon targets by reducing consumer demand through price. It also encompasses water resources planning with respect to system capacity and supply augmentation. Using London as a case study, we show that the inclusion of end-use interactions has a major impact on the projections of water sector requirements. In particular, future water demand per capita is lower, and less supply augmentation is needed than would be planned for without considering the interactions. We find that deep decarbonisation of electricity is necessary to maintain an acceptable quality of life while remaining within water and greenhouse gas emissions constraints. The model results show a clear need for consideration of the end-use level water-energy interactions in policy analysis. The modelling tool provides a base for this that can be adapted to the context of any industrialised country.